Prevalence of seed-borne Fusarium in local rice cultivars from Barishal district - Mubin, Md Mejbah Uddin; Khan, Abu Ashraf; Kader, Md Abdul; Masum, Md Mahidul Islam; Rahman, Md Mahbubur (Annals of Bangladesh Agriculture, 2023)
Seed-borne diseases cause substantial yield loss of rice every year. The present study was conducted to determine the status of seed-borne Fusarium spp. infection in farmers’ saved rice seeds of nine local cultivars collected from all ten upazila of Barishal district. Two fungal species of Fusarium, i.e., Fusarium fujikuroi, and Fusarium equiseti were identified based on morphological characteristics using the blotter method. The highest infection of F. fujikuroi was observed in Babuganj upazila (11.11%), followed by Agailjhara (8.83%). On the other hand, the highest infection of F. equiseti was observed in Bakerganj (8.17%), followed by Mehendiganj (8.05%). The lowest infection of F. fujikuroi and F. equiseti was observed in Muladi, with values of 5.22% and 4.54%, respectively. Among local cultivars, the highest infection of F. fujikuroi (7.11%) was observed in Lalpaika followed by Sakkhorkora (6.83%). On the other hand, the highest infection of F. equiseti was observed in Dudhmona (9.17%) followed by Kajalshail (8.94%). The lowest infection of F. fujikuroi and F. equiseti was observed in the Bhushihara cultivar with the same infestion (4.61%). The prevalence of Fusarium spp. varied with respect to the location of seed collection as well as cultivars. Highest seed germination was observed in Bhushihara (89%) followed by Swarna (87%) and Joyna (85%). Lowest seed germination was observed in Lalpaika (78%). The highest mortality of the seedlings after germination was observed in Lalpaika (24.25%), followed by Dudhmona (23%) and the lowest mortality of the seedlings was observed in Bhushihara (14.75%). Thus, seed germination rate and post-emergence mortality of seedlings were directly associated with seed-borne infection of F. fujikuroi and F. equiseti. Ann. Bangladesh Agric. (2023) 27 (2): 31-39